Increasing Students’ Reading Comprehension through Cognitive Strategies of Senior High School of Sidenreng Rappang Regency - elihami elihami (Lingua Cultura, 2017)
This research was a quasi-experimental research at the objective of finding the increasing students’ reading comprehension achievement through cognitive strategies (rehearsal, organization, and elaboration). It also aimed to find the extent to which these cognitive strategies influence the students’ reading comprehension achievement. The subject of the research was the Senior High School of Sidenreng Rappang Regency consisting of 50 respondents of two classes from 11 schools in Sidenreng Rappang. Each class consisted of 25 respondents; one class was the control and another class the tentative one. The data were collected through the reading comprehension test in pretest and posttest, and the observation checklist during the teaching and learning process. The test consisted of 45 items of the test from three kinds of text (news item, descriptive, and narrative). The observation checklist consisted of four statements for rehearsal strategies, three statements for organization strategies, and one statement for elaboration strategy. The research findings show that the students’ reading comprehension is increased for both groups from pretest to posttest. The experimental group is higher than the control one (60,6 > 50,1) and the t-test is greater than the P-Value (0,05 > 0,007), which means that there is a significant difference after giving treatment to the experimental group. The application of cognitive strategies also positively influences the increasing students’ reading comprehension achievement. Thus, it is concluded that the use of cognitive strategies is useful to increase students’ reading comprehension in teaching and learning words.